The effect of complex cognitive training on subsequent night sleep. (25th October 2019) - Cerasuolo, Mariangela; Conte, Francesca; Cellini, Nicola; Fusco, Giuseppina; Giganti, Fiorenza; Malloggi, Serena; Ficca, Gianluca
Summary: Using a nap design, we have recently shown that training at a complex cognitive task at bedtime improves objective sleep quality by reducing sleep fragmentation. In order to extend our findings to nighttime sleep, here we assess the impact of a multi‐componential cognitive task at bedtime on the subsequent sleep episode of subjects reporting habitual bad sleep, allegedly characterized by high sleep fragmentation. In a within‐subjects design, 20 subjective bad sleepers underwent polysomnographic recording in three conditions: (a) baseline sleep (BL); (b) post‐training sleep (TR), preceded by a complex ecological task, i.e. a modified version of the word game Ruzzle ; (c) post‐active control sleep (AC), preceded by a control task. Sleep in TR was more organized (higher number of cycles and longer time spent in cycles) and showed lower microarousal frequency than in AC and BL. As for sleep continuity (total and brief awakening frequency) and other stability measures (state transition and functional uncertainty period frequency, time in functional uncertainty), both TR and AC showed significant improvements compared with BL. Arousal frequency was also reduced in TR relative to BL. Our results show a clear impact of cognitive training on subsequent night sleep, basically consisting of an increase in sleep continuity, stability and organization. In our sample of bad sleepers, these post‐training changes end up representing a notable sleep improvement, also consistently reflected in subjective sleep quality perception. Therefore, ecological pre‐sleep cognitive training should be further studied as an easily accessible complementary approach in standard therapies for sleep‐disordered populations.